EMPIRICAL METHODS IN THE EVALUATION OF TECHNOLOGICAL PROCESSES - Remus Boboescu (Nonconventional Technologies Review)
: Experimental or empirical modeling is used in the study of processing processes using unconventional technologies. Empirical modeling means finding mathematical formulas that link the various sizes called influence factors to measured sizes or related to them through calculations called objective functions. The paper presents the particular aspects of the application of experimental modeling in the industrial environment. This differs from the one in research projects because it narrows the researched experimental field and requires the rapid obtaining of some results in order to make some decisions. An experimental modeling for laser cutting for glass-fibre epoxy sheets was carried out. The organization of the experimental plan is presented. A complete factorial experimental design 22 was expanded into classical experimental series and an experimental design 23. The experiments carried out showed that the main factors that intervene in the process to achieve the penetration of the material and establish the shape of the cut are the cutting speed and the thickness of the material.